Morning cortisol as an indicator of arterial stiffness in patients with type 2 diabetes: prospective cohort study and Mendelian randomization study - Hu, Zhuomeng; Sun, Lin; Peng, Ying; Shi, Juan; Guo, Yihua; Fang, Qianhua; Liu, Cong; Wei, Xing; Hong, Jie; Gu, Weiqiong; Zhou, Weiwei; Wang, Weiqing; et al. (Frontiers in Endocrinology, 2025)
IntroductionElevated cortisol levels have been linked to arterial stiffness, but the evidence for this association remains controversial. We aimed to elucidate this relationship and to explore potential mediation pathways.MethodsTo investigate the relationship between morning cortisol and arterial stiffness, two approaches were employed. First, we used linear mixed-effects (LME) models and mediation analysis in a prospective cohort study (n=1,235; average follow-up of 3.5 years) in type 2 diabetes (T2D), featuring repeated brachial-ankle pulse wave velocity (baPWV) measurements (2–8 per participant; 4,143 total) to assess arterial stiffness. Second, a two-step Mendelian randomization (MR) study was conducted using summary data of genome-wide association studies (GWAS) of CORtisol NETwork (CORNET) and UK Biobank (UKB). Arterial stiffness was measured by baPWV in the cohort study, with coronary atherosclerosis from UKB serving as the validation outcome.ResultsThe prospective study included participants with a mean age of 54.3 ± 11.3 years (65.3% male) and a mean baseline baPWV of 16.06 ± 3.23 m/s. It revealed that each 1-unit increase in log10Cortisol was associated with a 0.67 m/s (95% CI: 0.25–1.10, P = 0.002) increase in baPWV. Mediation analysis indicated that systolic blood pressure (SBP), diastolic blood pressure (DBP), and mean arterial pressure (MAP) all partially mediated the association between morning cortisol and arterial stiffness, with SBP contributing the largest proportion (18.68%, 95% CI: 16.48–23.66%; P = 0.033). The two-step MR analysis further supported that SBP could mediate the positive relationship between morning cortisol and coronary atherosclerosis.ConclusionsThis research provides both observational and genetic evidence indicating a potential causal relationship between morning cortisol and arterial stiffness, with SBP as a key mediator.